High strength natural lightweight aggregate concrete with silica fume - Yeginoball, A.; Sobolev, Konstantin G.; Soboleva, S. V.; Tokyay, Mustafa (American Concrete Institute, 1998)
High strength lightweight aggregate concretes are usually produced using special artificial aggregates together with mineral and chemical admixtures. Using natural lightweight aggregates instead of processed artificial aggregates can significantly reduce cost of such concretes. Turkey has rich reserves of volcanic tuff and pumice stones. In Turkish standards highest strength classes for lightweight tuff and pumice concretes are 30 and 16 MPa, respectively. In this research selected samples of these lightweight rocks were used to produce high strength lightweight aggregate concretes. The binding medium was made of pottland cement, silica fume and superplasticizing admixture. For each concrete mixture properties such as workability, unit weight, compressive st:rengtl1 at various ages, as well as splitting tensile strength, modulus of elasticity and thermal conductivity values were determined to find the optimum quantities of materials to be used. Tests show that it is possible to produce a natural lightweight aggregate concrete with a 28-day compressive strength of 55 MPa, a dry unit weight in the range of 1700-2100 kg/m3and coefficient of thermal conductivity value of about 0.55 W/m2K. Mathematical equations based on experimental results were obtained by regression analyses. The equations are useful for optimizing concrete mixtures for specified unit weight and compressive strength. © 1998 American Concrete Institute. All rights reserved.
6th CANMET/ACI/JCI Conference on FLy Ash, Silica Fume, Slag and Natural Pozzolans in Concrete - CANMET/ACI/JCI International Conference -- 1998-05-31 through 1998-06-05 -- Bangkok -- 170210
Keywords: Concrete; High-strength; Lightweight aggregate; Mix proportronmg; Modulus of elasticity; Pumice; Silica fume; Splitting tensile strength; Superplasticizer; Thermal conductivity; Unit weight